Epidorylaimus monhystera sp. n., an atypical species of the genus Epidorylaimus Andrássy, 1986 (Dorylaimida: Qudsianematidae) from Japan - Ahmad, Wasim; Imran, Zarrin; Araki, Masaki (Zootaxa, 2016)
Epidorylaimus monhystera sp. n. is described and illustrated from Japan. The new species is characterized by having 1.12-1.33 mm long body, lip region offset by slight constriction, odontostyle 15–16 μm and odontophore 18-20 μm long, guiding ring single, pharyngeal expansion gradual, vulva transvers, female genital system mono-opisthodelphic, anterior branch completely absent and tail elongated-conoid, ventrally arcuate. It is distinctive from all other species of the genus Epidorylaimus in having mono-opisthodelphic female genital system. Its relationship with other monodelphic genera of Qudsianematidae is also discussed and an emended diagnosis of the genus Epidorylaimus is provided with list of valid species, key for their identification and a diagnostic compendium.